Phytogenic additives and glutamine plus glutamic acid in broiler diets - Pelícia, V c [UNESP]; Stradiotti, A c [UNESP]; Araujo, P c De [UNESP]; Maruno, M k [UNESP]; Carvalho, F b De; Pezzato, Antonio Celso [UNESP]; Sartori, José Roberto [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2013)
The objective of this study was to evaluate the effect of the dietary supplementation of phytogenic additives (PAs) and glutamine plus glutamic acid (Gln/Glu), associated or not, in replacement of antibiotic growth promoters and anticoccidials (AGP/AC) on the performance and carcass yield of broilers. Five hundred male Cobb broilers were housed in an experimental house and randomly distributed into five treatments, with four replicates of 25 birds each. Treatments consisted of a control diet (CD); CD+AGP/AC; CD+Gln/Glu; CD+PAs; CD+Gln/ Glu+PAs. Diets were formulated only with plant feedstuffs, i.e., they did not contain any animal byproducts. Performance data were collected for the accumulated periods of 1-7, 1-21, and 1-42 days of age. Carcass yield and parts yield were determined at 42 days of age. Treatments did not influence performance during none of the evaluated periods. The greatest carcass yield (p<0.05) was obtained in birds in the treatments CD+Gln/Glu and CD+Gln/Glu+PAs relative to CD, but not different from birds in the AGP+AC and PAs treatments, which were not different from the CD treatment. Birds fed the CD+Gln/Glu diet presented greater breast yield (p<0.05) compared with those in the CD and AGP/AC treatments, but there was no difference in comparison with the other treatments. Under the conditions of the present experiment, the dietary supplementation with phytogenic additives and with glutamine plus glutamic acid does not affect the performance, but improves carcass yield and breast yield of broilers.
Keywords: Alternative additives; plant extracts; essential oils